Book Review: Bert Rosenbloom, Marketing Channels: A Management View. (December 2015) - Bansal, Ajay
Bert Rosenbloom, Marketing Channels: A Management View, India: Cengage Learning Publications, 2013, 660 pp. (paperback) ISBN: 978-81-315-1842-7.